Surgical treatment of infertility cervical incompetence. - Cancino, Heli (2015)
The gynaeco-obstetricians have oriented the exercise of our activities to the study and treatment of infertile couples, in rare cases not we have a marriage that recounts the anguish evident frustration carry a pregnancy to term that, a few weeks evolution, in the most unexpected and generally forms abruptly ends in spontaneous abortion. That is, that marriage, in our view, suffering a picture of infertility; for not having been completed the product of conception; unlike the infertile couple that fails to conception.